Studies on the gastric proteases in three South African snake species - Robertson, Sirion Sholto Douglas (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1987)
The pepsinogens and pepsins of cobra, mole snake and puff adder have been studied. The pepsinogens of all three species fall into two distinct groups, here designated PI and PII. At least the latter group, in all cases, shows substantial microheterogeneity. Physicochemical studies suggest that the cobra and puff adder PII groups are more similar to each other than either is to the mole snake PII group. Kinetic studies indicate that, in the cobra and mole snake, the PI and PII pepsins differ in their Arrhenius activation energies. Such difference is smaller, or absent, in the case of the puff adder PI and PII pepsins. These characteristics of the pepsins are assessed in the context of the differences between the oral secretions of the three species studied. The suggestion is advanced that the puff adder's strongly proteolytic venom has influenced certain properties of its gastric proteases.
Keywords: Snakes -- South Africa; Proteolytic enzymes; Pepsin; Pepsinogen